Book review: Ruchira Gupta (Ed.), River of Flesh and Other Stories: The Prostituted Woman in Indian Short Fiction. Issue 2 (December 2017) - Tiwari, Kusha
Ruchira Gupta (Ed.), River of Flesh and Other Stories: The Prostituted Woman in Indian Short Fiction . New Delhi: Speaking Tiger, 2016, 256 pp., ₹350.